STUDI AKTIVITAS INHIBITOR TIROSINASE DAN KADAR FENOLIK TOTAL EKSTRAK METANOL JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Nur Syamsi Dhuha; Nur Suci Suci Wahdaniya; Syamsuri Syakri (Jurnal Kesehatan, 2020)
Oyster mushroom (Pleurotus ostreatus) contains vitamin B, vitamin C and carbohydrates such as β-glucans, monoterpenoids, triterpenoids, potential sources of lignin and phenols. The presence of phenolic compounds indicates the ability of oyster mushrooms as potential antioxidants and anti-tyrosinases. Searching for depigmentation agents in cosmetics is necessary to ensure safety and reduce side effects. The aims of this study are to determine the inhibitory activity of tyrosinase and total phenolic levels of Pleurotus ostreatus methanol extract. Tyrosinase inhibitor activity was measured using the Enzyme Linked Immunosorbent Assay (ELISA) method at 490 nm with various concentrations, which were 55 ppm, 65 ppm, 75 ppm, 85 ppm and 95 ppm. Determination of total phenolic levels at a concentration of 100 ppm using a UV-Vis Spectrophotometer at 744.8 nm. Based on the research, the percentage of tyrosinase inhibitor of Pleurotus ostreatus methanol extracts at concentrations of 55 ppm, 65 ppm, 75 ppm, 85 ppm and 95 ppm were 17.6%, 19.5%, 22.2%, 25.9%, and 35.7%, respectively. The result of the IC50 and total phenolic content are 9.06% and 1.13%. These results exhibit that the methanol extract of Pleurotus ostreatus has a very strong tyrosinase inhibitor power.